History a novel - Morante, Elsa approximately 1912-1985 (Penguin Books, 2001)
This novel concerns a widowed Italian schoolteacher, Ida Mancuso, with a feckless teenaged son. After being raped by a German, she finds that the son she bears provides her only source of meaning amid universal catastrophe.